The silence of the sea : a thriller - Yrsa Sigurðardóttir (Yrsa Sigurðardóttir. þora Guðmundsdóttir., 2016)
"A luxury yacht crashes into a Reykjavik pier. But the boat is empty; no one is on board. What has happened to the crew? And what has happened to the family who were very much present when the yacht left Lisbon? What should Thora Gudmundsdottir, the series sleuth, make of the rumors that the vessel was cursed? She is spooked even more when she boards the yacht and thinks she sees one of the missing children. Where is Karitas, the glamorous young wife of the yacht's former owner? And whose is the body that has washed up further along the shore?"--